Assesment Social and Emotional Learning (SEL) Competence in Senior High School (SMA). - Luky Kurniawan; Muhammad Farozin (Indonesian Journal of Learning Education and Counseling, 2019)
This research aims to describe the social and emotional learning (SEL) competency requirement of senior high school (SMA) students. The data analysis technique in this research is descriptive data analysis and requirement questionnaire analysis. The subjects of this research were 192 of 10th grade senior high school students. The results of this research showed the development of social and emotional learning (SEL) competency was needed for 10th grade senior high school (SMA) students. Social and emotional learning (SEL) competency was reflected in self-awareness, self-management, social awareness, relationship skills, and responsible decision making. The requirement important substantiation for developing social and emotional learning (SEL) competency for senior high school (SMA) students are based on the requirement analysis result were obtained 80% for self-awareness, 69% for self-management, 73.5% for social awareness, 66% for relationship skills, and 82.5% for responsibility decision-making.